2020
DOI: 10.1007/s11605-019-04288-9
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Coverage Type Impacts Hospitalization Patterns Among Patients with Hepatopancreatic Malignancies

Abstract: Introduction: Disparities in health and healthcare access remain a major problem in the United States. The current study sought to investigate the relationship between patient insurance status and hospital selection for surgical care. Methods: Patients who underwent liver or pancreatic resection for cancer between 2004 and 2014 were identified in the National Inpatient Sample. The association of insurance status and hospital type was examined. Results: In total, 22,254 patients were included in the study. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…In particular, data have suggested racial disparities both in the utilization of surgical resection for patients with early‐stage pancreatic cancer, as well as receipt of chemotherapy 31,32 . Similarly, Mehta et al 33 has previously reported insurance status differences among patients undergoing hepato‐pancreatic surgery, with Medicaid patients being less likely to receive care at academic urban teaching hospitals. While other studies have focused on the volume‐outcomes relationship relative to individual quality metrics, the current study was the first to demonstrate a clear volume‐outcome relationship of PD volume with TOO.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, data have suggested racial disparities both in the utilization of surgical resection for patients with early‐stage pancreatic cancer, as well as receipt of chemotherapy 31,32 . Similarly, Mehta et al 33 has previously reported insurance status differences among patients undergoing hepato‐pancreatic surgery, with Medicaid patients being less likely to receive care at academic urban teaching hospitals. While other studies have focused on the volume‐outcomes relationship relative to individual quality metrics, the current study was the first to demonstrate a clear volume‐outcome relationship of PD volume with TOO.…”
Section: Discussionmentioning
confidence: 99%
“…Improved nurse‐to‐bed ratio may alleviate nurse workload and mitigate burnout, thus improving workplace satisfaction and performance 31 . Although not associated with TO in the current study, other structural measures such as hospital teaching status have been associated with TO 32,33 . Of note, the beneficial effect of these hospital “structural” factors were associated with improved odds of TO among both Magnet and non‐Magnet hospitals.…”
Section: Discussionmentioning
confidence: 54%
“…31 Although not associated with TO in the current study, other structural measures such as hospital teaching status have been associated with TO. 32,33 Of note, the beneficial effect of these hospital "structural" factors were associated with improved odds of TO among both Magnet and non-Magnet hospitals. In turn, patients undergoing HP surgery should focus on selecting hospitals that have strong structural measures in place to ensure "superior" clinical outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Используемые для этого интегральные модели объединяют несколь ко параметров в единый показатель, что позволяет унифицировать систему оценки качества хирургической помощи. Таким образом, создается предпосылка для сравнительной и системной оценки больших данных и систематизации мер по улучшению качества хирургии [1][2][3][4][5][6].…”
Section: вве де ниеunclassified
“…За последнее десятилетие число исследований, посвященных применению указанных моделей в онкологии и хирургии, растет [5,7,8,[11][12][13][14][15][16]. Авторы исследований полагают, что предлагаемые модели являются эффективным средством оценки качества хирургической помощи применительно к отдельным хирургам, хирургическим подразделениям и лечебным учреждениям, включая более широкие возможности для сравнительного анализа.…”
Section: вве де ниеunclassified